Lawyers in Digitalised Criminal Proceedings and Defendants’ Access to Criminal Justice - Anna Pivaty (Tilburg Law Review)
The majority of literature on digital criminal justice focuses on communication within the courtroom. By contrast, this article discusses the possible implications of digitalization of criminal proceedings for (legally represented) defendants’ access to criminal justice in general. In addition to communications during virtual hearings, it also discusses what happens before and after them. Defence lawyers act as vehicles for access to criminal justice, especially for detained suspects. Therefore, this article focuses on the lawyer-client relationship and their role in digitalised criminal justice. This reflection is based on qualitative interviews with 20 Dutch criminal lawyers as part of a broader study on the impact of digitalisation on the role of criminal defence lawyers. As a conclusion, it recommends that lawyers’ regulatory bodies address new dilemmas relating to legal representation in digitalised criminal proceedings.